Natural toxicants affecting animal health and production - Abdullah, Abdul Salam (Universiti Pertanian Malaysia, 1994)
Disease is one of the major constraints in animal production and causes a loss of capital in the form of direct and latent costs. The outbreak of haemorrhagic septicaemia in 1989 in Kinta Valley alone resulted in an estimated loss of RM500,000.00. The direct cost is the actual loss of capital in terms of veterinary therapy, culling and mortality. The direct cost is easily calculated and rapidly recognised by the farmers. However, it is much more difficult to quantify the real latent cost of diminished production due to physical malformations, abortions, photosensitisation and reduction of growth. It is impossible to assign a precise economic value of these losses for the livestock, industry.